Modeling fuel consumption in various external vehicle conditions for military vehicle using mixed linear models - Muhammad Nuraliffudin Saputra; Samsul Arif; Fakhri Wijanarko; Vishal R Panse; Agnes Sprakezia Lubis; Ro'fah Nur Rachmawati (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2023)
With the crisis in fuel consumption, it is necessary to save fuel consumption by selecting fuel that is quite efficient. The aim of the research is to examine the fuel consumption patterns of vehicles in an area that experiences various weathers so as to determine the level of efficiency of fuel use. both from the factor of fuel type, distance, speed, temperature, to the weather. testing was carried out using the linear model technique, the Linear Mixed effect model, and the Anova mathematical model. The results of the analysis if the different types of fuel have a very large significant effect in influencing the fuel consumption of a vehicle. With all the approaches analyzed from the linear mix model, analysis of variance and linear mix random effect model, the results show that other independent variables such as average speed, distance traveled and ambient temperature do not have much effect on fuel consumption. Based on modeling results that has been done, it can be identified if fuel consumption is strongly influenced by the type of fuel used by the vehicle. Meanwhile, other variables such as vehicle mileage, average speed, and ambient temperature at the time of data collection did not show any significant effect on fuel consumption.